Bioconversion of Ginsenosides from Red Ginseng Extract Using Candida allociferrii JNO301 Isolated from Meju - Lee, Sulhee; Lee, Yong-Hun; Park, Jung-Min; Bai, Dong-Hoon; Jang, Jae Kweon; Park, Young-Seo (Mycobiology, 2014)
Red ginseng (Panax ginseng), a Korean traditional medicinal plant, contains a variety of ginsenosides as major functional components. It is necessary to remove sugar moieties from the major ginsenosides, which have a lower absorption rate into the intestine, to obtain the aglycone form. To screen for microorganisms showing bioconversion activity for ginsenosides from red ginseng, 50 yeast strains were isolated from Korean traditional meju (a starter culture made with soybean and wheat flour for the fermentation of soybean paste). Twenty strains in which a black zone formed around the colony on esculin-yeast malt agar plates were screened first, and among them 5 strains having high β-glucosidase activity on p-nitrophenyl-β-D-glucopyranoside as a substrate were then selected. Strain JNO301 was finally chosen as a bioconverting strain in this study on the basis of its high bioconversion activity for red ginseng extract as determined by thin-layer chromatography (TLC) analysis. The selected bioconversion strain was identified as Candida allociferrii JNO301 based on the nucleotide sequence analysis of the 18S rRNA gene. The optimum temperature and pH for the cell growth were 20~30℃ and pH 5~8, respectively. TLC analysis confirmed that C. allociferrii JNO301 converted ginsenoside Rb1 into Rd and then into F2, Rb2 into compound O, Rc into compound Mc1, and Rf into Rh1. Quantitative analysis using high-performance liquid chromatography showed that bioconversion of red ginseng extract resulted in an increase of 2.73, 3.32, 33.87, 16, and 5.48 fold in the concentration of Rd, F2, compound O, compound Mc1, and Rh1, respectively.